Breeding for the improvement of indigenous chickens of Bangladesh: performance of foundation stock (Asian Journal of Medical and Biological Research, 2017)
Selection is one of the vital tools for improving the indigenous chicken genetic resources. A total of 1585-day-old chicks comprising of 3 types of chicken namely Naked Neck (NN), Hilly (H) and Non-descript Deshi (ND) were hatched for this study to form foundation stock. Improvement target of egg weight was to increase by 1g and improvement target of egg production rate was to increase by 2 % per generation. In foundation stock, selection was practiced at 40-week of age, on the basis of an index comprising the parameters of age at first egg (ASM), body weight(BW), egg production(EP) and egg weight(EW). Data were analyzed in CRD by General Linear Model (GLM) Univariate Procedure. Significantly highest fertility (82.71%) and hatchability (82.20%) were found in ND genotype. Significantly (P0.05) variation in FCR among the native chicken genotypes. NN genotype (3.46%) had non-significantly (?2 = 3.62; P > 0.05) higher chick mortality than ND (1.63%) and H (2.11%) at brooding period (0-4 weeks). Significantly (P